Halter ve polimetrik çalışmaların hızlanmaya etkisi - Kahramanoğlu, Çağlar (My University, 2007)
Created by trial version, http://www.pdf-convert.com SUMMARY Effect to Acceleration of Weight lifting and Polymetric Exercise Speed section which is being second phase of the sprint events is one of the most vital property that ascertain a sprinter quality. f a sprinter reach a top speed level in shortest tıme, he can get chance to run very good result. This investigation had done for searching weight lifting and the plyometrics movements effect to the sprint event. Also this working aims to form track and field model for whole sports branch about sprint, coming from pozitif benefits on accelaration. t’s aims to form all sport events a training model-this investigation had been between march 2006 and june 2006 . n this investigation at between 18 to 30 age groups, including 10 female and 20 male athlete, join to this investigation. This investigation had took twelwe week and during that period time totaly three various test has been done. Before section, middle of the section and end of the section, saved results has been made in the SPSS program. 1- Weight Lifting Power Test 2- Jump (Horizantal-Vertical) Test 3- Speed (0-40m) Test At the end of the investigation that is made utilize, weight lifting and polimetric movements which is apply together have observed to positive affects. So weight lifting and the polimetrics movements must be applied together and it may suggest to take part to whole sport branch which is interested with the speed section.
Keywords: Beden Eğitimi ve Spor; Halter_Fiziki Durum; Koşu_Spor; Spor